One Health scientific conference: International practices and lessons learned for Vietnam - Vietnam One Health Partnership; International Livestock Research Institute (International Livestock Research Institute, 2024)
The definition of One Health by the One Health High Level Expert Panel (OHHLEP, 2021) emphasizes One Health as an integrated and unifying approach, requiring the collaboration and efforts of multiple sectors, disciplines, and communities to address and sustainably balance and optimize the health of people, animals, and ecosystems. In addition, the Quadripartite organisations including the Food and Agriculture Organization of the United Nations (FAO), the World Organisation for Animal Health (WOAH), the UN Environment Programme (UNEP), and the World Health Organization (WHO), have signed a Quadripartite agreement, which will facilitate the actions for One Health at different levels. At the global level, One Health links to different aspects related to health (such as international health regulation-WHO), trade (the spread of zoonoses through international trade in animals and animal products, WTO), and climate change (UNEP, from various COPs 26–28) toward the contribution to the UN Sustainable Development Goals.